Association between relative fat mass and osteoarthritis in American adults - Li, Ziyuan; Yin, Tangchen; Chen, Yijing; Huang, Jiangsheng; Jiang, Yuanyue; Deng, Wei (Frontiers in Nutrition, 2025)
BackgroundRelative fat mass (RFM) is a newly established anthropometric measurement that offers an alternative method for assessing body fat. Osteoarthritis (OA) is a widespread public health issue, with existing evidence identifying obesity as a notable risk factor for the OA development. This study aimed to examine the potential correlation between RFM and OA within a nationally representative population.MethodsThis study employed data collected from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Weighted logistic regression models were performed to assess the relationship between RFM and OA. Furthermore, the predictive efficacy of various adiposity indicators for OA was examined through receiver operating characteristic (ROC) curve analysis, allowing for comparisons of area under the curve (AUC) values.ResultsThe study cohort comprised 28,535 participants from the NHANES dataset. The analytical results indicated significant positive associations between RFM and OA. Stratified analyses revealed notable effect modifications based on age and diabetes status concerning the RFM-OA relationship. Comparative ROC analysis indicated RFM exhibited a superior capability for predicting OA prediction (AUC values: 0.646) compared with traditional obesity metrics.ConclusionThe findings demonstrated a significant positive correlation between RFM and OA, indicating that higher RFM levels are associated with increased risk of OA. ROC analyses reinforced the diagnostic value of RFM for OA, with its predictive performance exceeding that of conventional adiposity metrics.